RAHASIA TAHAJJUD UNTUK MENINGKATKAN KECERDASAN SPIRITUAL, EMOSIONAL, DAN INTELEKTUAL (Telaah PemikiranYazid al-Bustomi) - Syamsuddin, -; Afroyim, Khunainah (Al Tadib : Jurnal Ilmu Pendidikan, 2017)
Ibn Manzur in Lisanul 'Arob explained, said ھجد الرجل "hajada ar rojulu", which means a person that sleeps at night. The word متھجد "mutahajjid" are people who wake up from sleep to perform prayers. In summary, understanding Tahajjud prayer is sunnah prayer done by someone after he wake up at night even though only briefly short time. If analyzed carefully so it is apparent that tahajjudis very useful to improve the intelligence of the spiritual, emotional, and intellectual. The goal of this study is to give direction to solve the problem as follows: To know the effect of tahajjud in improving spiritual, emotional,and intellectual intelligence.The method used in this research is a kind of library research and also phylosophy research that depart from theories or terms which are common to the next to the realities specific to get a new conclusion. The result of the study: (1) because tahajjud is worship of the most special then tahajjud done with full sincerity will be able to resolve the problems in our lives. (2) Tahajjud which is done sincerly, can bring peace of mind as well as mind therapy. (3) Enhance spiritual intelligence in ESQ 165 initiated by Ary Ginanjar Agustian known the term Zero Mind Process (ZMP). (4) prayer tahajjud can also increase intelligence. This is influenced by the alpha wave that brought us into the subconscious mind during sleep. Keywords: Tahajjud, spiritual intelligence, emotional intelligence, intellect